Acute myocardial infarction caused by persistent coronary spasm associated with high-grade macrophage accumulation. Issue 3 (17th March 2020) - Wakabayashi, Kohei; Nishikura, Tenjin; Shinke, Toshiro; Tanno, Kaoru
Abstract : The mechanisms responsible for persistent and lethal coronary spasm remain incompletely understood. Our group treated a patient with non-ST-elevation myocardial infarction (MI) caused by a spontaneously persistent spasm associated with high-grade macrophage accumulation. A 48-year-old man was transferred to an emergency room because of persisted chest tightness. The patient's chest pain subsided without ST elevation when he arrived at the hospital, but he tested positive for fatty acid-binding protein. Emergent coronary angiography revealed a subtotal occlusion in the middle of the right coronary artery. The occluded lesion was released immediately after an injection of isosorbide dinitrate. No disruption, ulceration or erosion was observed at the culprit lesion segment on optical coherence tomography. The only finding was high-grade macrophage accumulation in the segment of the persistent focal coronary spasm. The present case suggests that the early stage of atherosclerosis with high-grade macrophage accumulation was associated with persistent coronary spasm resulting in acute MI.